2013
DOI: 10.2105/ajph.2012.301102
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers in Low- and Middle-Income Countries: What Do We Know About Scaling Up and Sustainability?

Abstract: Scaling up and sustaining CHW programs in LMICs requires effective program design and management, including adequate training, supervision, motivation, and funding; acceptability of the program to the communities served; and securing support for the program from political leaders and other health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
262
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(279 citation statements)
references
References 32 publications
12
262
0
5
Order By: Relevance
“…These findings suggest that, as with other communitybased programmes, focus should be given to maintaining motivation of community-based staff (37,38) . The Ethiopian programme is implemented within national health systems with limited resources.…”
Section: Discussionmentioning
confidence: 76%
“…These findings suggest that, as with other communitybased programmes, focus should be given to maintaining motivation of community-based staff (37,38) . The Ethiopian programme is implemented within national health systems with limited resources.…”
Section: Discussionmentioning
confidence: 76%
“…17 A recent meta-analysis showed that one of the most important aspects of scalable interventions with CHWs is community acceptance. 18 Although some studies have demonstrated that iCCM interventions are acceptable to the community, 19,20 others have shown that programs are resisted if CHWs do not provide services of value. 21 This is important because iCCM programs, which have low utilization and likely low acceptance of services are the least costeffective, do not lead to decreases in mortality, and may decrease demand for biomedical health care, leading the most marginalized to seek care from ineffective providers.…”
Section: Introductionmentioning
confidence: 99%
“…This professional, drawn from the community itself, is responsible for regular home visits, establishing the link between residents and the FHS team, and helping to improve the latter's actions regarding health determinants 5 . Numerous benefits of these professionals have been reported, particularly in low-to-middle income countries 6 . With regard to the population served, each FHS team is responsible for 4,000 persons at most versus 12,000 persons/team under the traditional model, in which there must be sufficient CHW to serve 100% of the registered population.…”
Section: Introductionmentioning
confidence: 99%